Effect of air velocity on heat transfer characteristics of curd during cooling in High Impact Polystyrene cups - A R, Krishnendu; Dabas, J K; Sinha, Chitranayak (Indian Journal of Dairy Science, 2019)
Transient cooling process of curd in High Impact Polystyrene cup was studied for different values of cooling air velocity and flow direction (radial and axial). Exponential cooling curves for dimensionless temperature of curd were obtained from scanned data. Biot number and surface heat transfer coefficient were analytically calculated from values of cooling factor and lag factor obtained from cooling curves. It was found that surface heat transfer coefficient increases, and cooling time decreases significantly during initial increase in air velocity from 0.5 m s-1. However, this positive effect reduces at higher air velocities, greater than 4 m s-1. The reason is that the inner heat transfer resistance of curd remains unaffected by air velocity. This is evident from the calculated values of Biot number in the range of 4 to 5. The given study is helpful to the designer of cooling equipment for curd cups or containers.